Analisis Penjadwalan Proyek Terhadap Waktu Penyelesaian Proyek Pada Wisma Koperasi Sugri di Rangkasbitung - Bambang Pujo Purwoko; Siti Aminah; Jauhar latifah; Andri Susilo (E-Journal Studia Manajemen, 2012)
The aim of the study to determine how the process of project scheduling and project completion time. Analysis of projects using PERT (Program Evaluation Review Technique). To determine the time of completion using the two calculations, forward and backward calculation. From all calculations start from ground, first, second and the third floor, note that all activities of critical experience caused delayed completion of the project. Thus there is effect on project schedule project on completion time of project.